CEO OVERCONFIDENCE DAN KONSERVATISME AKUNTANSI TERHADAP MANAJEMEN LABA: SEBELUM DAN SESUDAH PANDEMI COVID-19 - Adiman, R Multi K; Afag, Richa Rachmawati; Tyas, Ratih (Journal of Sustainable Transformation, 2025)
COVID-19 has impacted by decreasing tourism, hotel, and restaurant revenue. However, at the end of 2020, the share price in the tourism sector showed a positive trend, causing a big question mark for researchers. This study examined the difference in term of CEO overconfidence and earnings management before and after COVID-19. The quantitative method was used with secondary data taken from the financial statements of the tourism, hotel, and restaurant sectors. The data was then analyzed by paired samples t-test analysis. The findings of this study indicate that CEO overconfidence did not significantly affect earnings management in 2018-2019 before the pandemic and CEO overconfidence also did not significantly affect earnings management in 2020-2021 during the pandemic. This shows that the COVID-19 event did not change a manager's behavior.